PENGOLAHAN NATA DE COCO MENGGUNAKAN SKIM DAN AIR KELAPA TANPA NITROGEN TAMBAHAN - Cica Riyani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
Nitrogen is an additional material used in the processing of nata de coco which functions as a protein provider for the formation and proliferation of bacterial cells which will affect the formed cellulose. The purpose of this study was to determine how to process nata de coco using skim and coconut water without adding a nitrogen source. The treatment tested in this study is a variety of substrates, namely coconut water subtrate (Sa), coconut water and coconut milk skim subtrate (Sb), and coconut milk skim subtrate (Sc). The treatments were arranged in a completely randomized design with three replications. Observations were made on the yield, weight and thickness of the nata. The results showed that the yield, weight, and thickness values of nata de coco were influenced by the treatment being tested. The best results were obtained from treatment (Sa) which resulted in a yield of 54.50%, nata weight of 600 grams, and thickness of 1.7 cm.Keywords : Nata de coco, coconut water, coconut milk skim, nitrogen free